การพัฒนาและประยุกต์ใช้อะลูมิเนียมอะโนไดซ์เป็นตัวดูดกลืนรังสีอาทิตย์ในตัวเก็บรังสีอาทิตย์แบบท่อสุญญากาศ: Development and Application of Anodized Aluminium for Selective Absorber in Evacuated Tube Collector (ETC) - Nunocha, Pornnipa; Suriwong, Tawat; Threrujirapapong, Thotsaphon (Asian Health, Science and Technology Reports, 2014)
งานวิจัยนี้เป็นการประยุกต์ใช้แผ่นอะลูมิเนียมที่ผ่านกระบวนการทาฟิล์มอะโนไดซ์ที่มีผงนิกเกิล (Ni-Al2O3) หรือแผ่นอะลูมิเนียมอะโนไดซ์ มาเป็นตัวดูดกลืนรังสีอาทิตย์ในตัวเก็บรังสีอาทิตย์แบบท่อสุญญากาศแบบ 2 ชั้น โดยท่อแก้วสุญญากาศไม่มีการเคลือบสารเลือกรับรังสีอาทิตย์ โดยเปลี่ยนตาแหน่งของการเคลือบจากเดิมที่เคลือบที่ผิวแก้วท่อชั้นใน มาเป็นเคลือบที่แผ่นอะลูมิเนียม แผ่นอะลูมิเนียมอะโนไดซ์มีการวิเคราะห์หาเฟส สัณฐานวิทยา และค่าการดูดกลืนรังสีอาทิตย์ด้วยเทคนิค ด้วยเครื่อง X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), Energy Dispersive Spectrometry (EDS), และ Ultraviolet-Visible-Near Infrared Spectrometer การทดสอบประสิทธิภาพเชิงความร้อนตัวเก็บรังสีอาทิตย์ () ที่มีการใช้แผ่นอะลูมิเนียมอะโนไดซ์มาเป็นตัวดูดกลืนรังสีอาทิตย์ ตามมาตรฐาน ISO 9806-1 ผลการทดลอง พบว่า ค่าการดูดกลืนรังสี () และค่าการสะท้อนรังสี (R) ของแผ่นอะลูมิเนียมอะโนไดซ์มีค่า 0.94 และ 0.06 ตามลาดับ ความหนาเฉลี่ยของชั้นฟิล์มอะลูมิเนียมอะโนไดซ์เท่ากับ 11.8 ไมโครเมตร ผลการประเมินค่าประสิทธิภาพทางความร้อนสูงสุด (max) มีค่าเท่ากับ 0.72 และ 0.69 สาหรับกรณีที่พิจารณาว่าสัมประสิทธิ์การสูญเสียความร้อนรวม (UL) มีค่าคงที่ และไม่คงที่ ตามลาดับ The objective of present research is focused on to apply the Ni-pigmented on aluminium oxide films or anodized aluminium (Ni-Al2O3) through anodizing process as solar absorber in evacuated tube collectors (ETC). In this study, double layers evacuated tube was used without coating solar on outer surface of the inside glass vacuum tube. The solar absorber was coated on aluminium sheets. Anodized aluminium was characterized phase, morphology and solar absorbtance by X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), Energy Dispersive Spectrometry (EDS) and Ultraviolet-Visible-Near Infrared Spectrometer. Collector thermal efficiency () for using the aluminium anodized as solar absorber in ETC were evaluated, according to ISO 9806-1. In the results, absorbtance () and reflectance (R) of sample were 0.94 and 0.06, respectively. The average thickness of Ni-Al2O3 films was 11.8 m. The maximum thermal efficiency (max) of solar collector was 0.72 and 0.69 for constant and non-constant of the overall heat loss coefficient (UL), respectively.